2019
DOI: 10.22153/kej.2019.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Silica MCM-41 as a Carriers Material for Nystatine Drug in Delivery System

Abstract: In the present study, MCM-41 was synthesis as a carrier for poorly drugs soluble in water, by the sol-gel technique. Textural and chemical characterizations of MCM-41 were carried out by X-ray diffraction (XRD), Fourier transform infrared (FTIR), scanning electron microscope (SEM), and thermal gravimetric analysis (TGA). The experimental results were analyzed mesoporous carriers MCM-41. With maximum drug loading efficiency in MCM-41 determined to be 90.74%. The NYS released was prudently studied in simulated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Si-OH has a broad peak between 3000 and 3900 cm1; O-H bending peaks are found at 3551 and 3402 cm -1 . The absorption band at 1599 cm -1 and 1629 cm -1 was ascribed to the alkyl group's C-H stretching vibration, which was observed in the spectrum of MCM-41 [38]. The bands were also observed in Broyer et al [39] and Grecco et al [40].…”
Section: Ftir Spectra 33mentioning
confidence: 72%
See 1 more Smart Citation
“…Si-OH has a broad peak between 3000 and 3900 cm1; O-H bending peaks are found at 3551 and 3402 cm -1 . The absorption band at 1599 cm -1 and 1629 cm -1 was ascribed to the alkyl group's C-H stretching vibration, which was observed in the spectrum of MCM-41 [38]. The bands were also observed in Broyer et al [39] and Grecco et al [40].…”
Section: Ftir Spectra 33mentioning
confidence: 72%
“…The kinetic study demonstrated that the Langmuir isotherm was the closest fit. Ibrahim [38] investigated the desulfurization of commercial diesel fuel using activated carbon. He found that the residual sulfur level of diesel fuel was reduced from 580 to 247 ppm, resulting in a desulfurization efficiency of 57%.…”
Section: Introductionmentioning
confidence: 99%
“…Asymmetric stretching vibrations of Si-O-Si bonds are present between 984 and 1100 cm −1 , while Si-O-Si bending vibrations are present between 458 and 796 cm −1 . The peaks around 1428 and 1470 cm −1 are attributed to the C-O bond vibrations of CaCO 3 which are more intense in MTA and Ca-doped MSNs powder groups due to the presence of more calcium ions [16,[25][26][27].…”
Section: Fourier-transform Infrared Spectroscopy (Ft-ir)mentioning
confidence: 99%
“…around 1428 and 1470 cm −1 are attributed to the C-O bond vibrations of CaCO3 whi more intense in MTA and Ca-doped MSNs powder groups due to the presence of calcium ions [16,[25][26][27].…”
Section: Fourier-transform Infrared Spectroscopy (Ft-ir)mentioning
confidence: 99%
“…Mesoporous silica has attracted the attention of researchers in the field ever since its discovery by the Mobil Corporation due to its special properties, high specific surface area, large pore volume, easy functionalization and high biocompatibility. Generally, mesoporous silica can be easily obtained by using a cationic surfactant as a template, which serves as a structure-directing agent for silica polycondensation (a silica source) through electrostatic interactions [ 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%